The Australian and New Zealand Intergenerational Cohort Consortium: a study protocol for investigating mental health and well-being across generations. (1st April 2020) - Olsson, Craig A; Spry, Elizabeth; Letcher, Primrose; McAnally, Helena; Thomson, Kim; Macdonald, Jacqui; Greenwood, Chris; Youssef, George; Romaniuk, Helena; Iosua, Ella; Sligo, Jude; Hutchinson, Delyse; et al.
Abstract : The Australian New Zealand Intergenerational Cohort Consortium (ANZ-ICC) brings together three of the longest running intergenerational cohort studies in Australia and New Zealand to examine the extent to which preconception parental life histories (from infancy to parenthood) predict next generation early health and development. The aims are threefold: (1) to describe pathways of advantage that strengthen emotional health and well-being from one generation to the next, (2) to describe pathways of disadvantage that perpetuate cycles of emotional and behavioural problems across generations, and (3) to identify modifiable factors capable of breaking intergenerational cycles. The Victorian Intergenerational Health Cohort Study has followed 1, 943 young Australians from adolescence to adulthood across ten waves since 1992, and 1, 030 offspring from pregnancy to early childhood since 2006. The Australian Temperament Project Generation 3 Study has followed 2, 443 young Australians from infancy to adulthood across 15 waves since 1983, and 1170 offspring from pregnancy to early childhood since 2012. The Dunedin Multidisciplinary Health and Development Study Parenting Study has followed 1, 037 young New Zealanders across 15 waves since 1972, and 730 offspring in early childhood since 1994. Cross-cohort replication analyses will be conducted for common preconception exposures and next generation offspring outcomes, while integrated data analysis of pooled data will be used for rare exposures and outcomes. The ANZ-ICC represents a unique collaboration that bridges the disciplines of lifecourse epidemiology, biostatistics, developmental psychology and psychiatry, to study the role of parental preconception exposures on next generation health and development.